TiO2−x films for bolometer applications: recent progress and perspectives. (1st January 2022) - Zhang, Qiming; Yan, Ruiyang; Peng, Xiaoyan; Wang, YuShui; Feng, Shuanglong
Abstract: The bolometer is widely used in military and civilian infrared imaging due to its advantages of non-cooling, small size and portability. Thermosensitive materials seriously affect the performance of bolometers. As a kind of heat-sensitive material, the TiO2−x material has the advantages of good thermal stability, large-area preparation, and compatibility with the complementary metal-oxide semiconductor (CMOS) process. However, there is almost no review on the application of titanium oxide for bolometers. In this paper, we introduce the bolometer's main thermal and photoelectric performance parameters and the critical technologies to manufacture the bolometer. Finally, we will particularly emphasize the effects of preparation process parameters of TiO2 on the performance parameters temperature coefficient of resistance (TCR), 1/ f noise, etc.